Strategi Pembelajaran Perkembangan Kognitif untuk Anak Usia 4-6 Tahun: Analisis Bibliometrik 2023 - Irens Sadin; Ledia Rizkika; Silvani Ruhiyat; Chandra Nurul Khojanah; Indri Rahmawati; RR. Deni Widjayatri (UIN Mataram, 2023)
The objective of this analysis is to analyze how research on cognitive development learning strategies for 4-6 year olds and to find out what topics might variable future research. Analysis methods are a library review using the bibliometric literacy study approach and publication or publication application with Google scholar as database. After results were degenerated by selecting specific subjects on 'cognitive development for preschool children 4-6 years,' i related article was obtained for review from 900 preliminary search articles. Then colled a meta data application VOSViewer used to create a research trend visualization. Studies show that the classification analysis of cognitive development learning strategies for 4-6 year-olds is divided into 9 clusters. (Red, Green, Dark Blue, Yellow, Purple, Light Blue, Orange, Brown, Pink).